2014
DOI: 10.1016/s0968-8080(14)43791-1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of completion of early medical abortion using a text questionnaire on mobile phones compared to a self-administered paper questionnaire among women attending four clinics, Cape Town, South Africa

Abstract: In-clinic follow-up to assess completion of medical abortion is no longer a requirement according to World Health Organization guidance, provided adequate counselling is given. However, timely recognition of ongoing pregnancy, complications or incomplete abortion, which require treatment, is important. As part of a larger trial, this study aimed to establish whether women having a medical abortion could self-assess whether their abortion was complete using an automated, interactive questionnaire on their mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…1 We draw on a "medicalization" framework 2,3 to describe the spectrum of approaches to the management of medical abortion ranging from most medicalized to least medicalized. Shifts towards less medicalized care can include: the administration of misoprostol in clinic but the option for women to be discharged to manage the process of expulsion at home; 4,5 the option to selfadminister misoprostol at home after the clinical administration of mifepristone; 6,7 the option to administer both misoprostol and mifepristone at home; and replacing follow-up with remote monitoring/self-assessment of abortion completion, for example via mobile phones, 8 or the independent use of self-assessment cards and pregnancy tests. 9,10 In this review, we focused exclusively on firsttrimester medical abortion.…”
Section: Introductionmentioning
confidence: 99%
“…1 We draw on a "medicalization" framework 2,3 to describe the spectrum of approaches to the management of medical abortion ranging from most medicalized to least medicalized. Shifts towards less medicalized care can include: the administration of misoprostol in clinic but the option for women to be discharged to manage the process of expulsion at home; 4,5 the option to selfadminister misoprostol at home after the clinical administration of mifepristone; 6,7 the option to administer both misoprostol and mifepristone at home; and replacing follow-up with remote monitoring/self-assessment of abortion completion, for example via mobile phones, 8 or the independent use of self-assessment cards and pregnancy tests. 9,10 In this review, we focused exclusively on firsttrimester medical abortion.…”
Section: Introductionmentioning
confidence: 99%
“…In some settings, hotlines or text messaging have been introduced and in one recent study, was demonstrated to be useful 39. Women who received texts for support during home misoprostol, after mifepristone administration in clinic, had significant reductions in anxiety and stress during the termination process 39.…”
Section: Discussionmentioning
confidence: 99%
“…However, published literature indicated that self-assessment of medical abortion based on symptoms alone was not reliable [6, 9, 10], and recently the WHO recommended that self-assessment of medical abortion outcome by women should utilize suitable pregnancy tests and checklists [11]. Multi-level (hCG detection thresholds >25, >100, >500, >2000 and >10,000 milli-international units/mL) and dual-level low-sensitivity pregnancy tests (hCG detection thresholds >5 and >1000 or >2000 milli-international units/mL), supplemented by checklists have shown promising results in the US [12], Europe [4, 13ā€“16] and some low- and middle income countries [3, 6, 17, 18].…”
Section: Introductionmentioning
confidence: 99%